The future of low fat low sugar ice cream technology strategies for enterprise building through scenario building - Adona, Charlie E. (University of the Philippines Diliman, 2010)
Today, under the heat of the sun, one could not just ignore the urge to have a super cold if not a frozen snack/dessert to soothe the irritating feeling that the environmental temperature gives us. It is also for this reason that a growing number of cold drinks and frozen delights are flooding the market. Among these is the ice cream made and eaten in almost every country in the world. Ice cream can be mass-produced and thus is widely available in developed parts of the world. It can be purchased from supermarkets and grocery stores, ice cream shops, convenience stores, and in small carts or vans. It is enjoyed as a flavored frozen desert treat made by freezing a pasteurized mix composed of a combination of milk products, sugar, water, flavoring and other optional ingredients. These tasty additions boost the fat, calories and carbohydrates content which many health conscious and diabetic persons do not want. Given that there a lot of diabetic and health conscious consumers nowadays, the FNRI-DOST came up with the idea of producing the Low Fat Low Sugar Ice Cream which creates frozen treat option that tastes great and does not compromise the health eating habits of ice cream. Low Fat Ice Cream has good benefits to human health and has a good potential in terms of marketability; this is because ice cream consumption is currently surging up in the Philippines, spurred on by the rising population. A scenario building however, gives additional direction and vision for this kind of technology. It describes what the low fat low sugar ice cream technology does and how this technology builds-up enterprises. This scenario building will also serve as a tool for policy makers and technology managers. Hopefully, this will result to more collaborators, inventors and partners for the commercialization of the technology. This study conducted, envisions "enterprise building, awareness and market acceptability of the Low Fat Sugar Ice Cream Technology". Participants which have experiences from Food Companies will conduct and develop scenarios that would lead to the attainment of the vision and mission, and will be presented in the grand scenario. Environmental scanning thru STEEP and SWOT analysis were conducted by the participants which resulted to many challenges that the low fat sugar ice cream technology would face. These are : 1) Market : Acceptability and Awareness, 2) Quality : Shelf-life and Safety, 3) Raw Materials, 4) Technology : capability, 5) Packaging, and 6) Government Support. The participant came up with twenty (20) predictable variables and four (4) uncertainties to build up the scenarios for the low fat sugar ice cream technology. From the variables, four clusters were formed as follows : Cluster 1 : Technological requirements; Cluster 2 : Regulatory System; Cluster 3 : Market Trends; and Cluster 4 : Culture. The clustered predictable variables and uncertainties were ranked according to their importance (impact) and degree of uncertainty with relevance to the vision. The overall ranking was used to develop a scenario logic with the aid of MS Office Excel (scattered chart type). This scenario logic produced was considered in developing of scenarios about the future of low fat low sugar ice cream technology in accordance with the vision of this scenario building. Two scenarios were considered from the scenario logic, scenario 1 is food fitness trip and scenario 2 is the Rule of LAW fat low sugar ice cream know-how. From these two scenarios the participants came up with a grand scenario "an enterprise-accepted ice cream served not only in the Philippines but also internationally with its globally-accepted quality, international appeal and convenient packaging". The ways and means or strategies to commercialize the LFLS Ice Cream Technology were identified. The foresight or scenario building can help to attain the vision, to enhance awareness and acceptability of low fat low sugar ice cream and to have an enterprise building of this technology. The team concludes that two scenarios, with high uncertainty, high impacts are plausible scenarios that can facilitate the development of strategies in commercialization of this technology. With the help and cooperation of the DOST, other government agencies concerned, and key players, this technology would have a promising future in five years time.